Adolescents With Autism Spectrum Disorder and Anorexia Nervosa Comorbidity: Common Features and Treatment Possibilities With Cognitive Remediation Therapy and Oxytocin - Plemeniti Tololeski, Barbara; Suhodolčan Grabner, Ana; Kumperscak, Hojka Gregoric (Frontiers in Psychiatry, 2021)
Autistic traits or autism spectrum disorder (ASD) can be found in 4 to 52 percent of anorexic patients, which makes the treatment of these patients very challenging. In this review, possible ways to treat ASD and anorexia nervosa (AN) comorbidity in children and adolescents are summarized. Over recent years, the focus has shifted from searching for the evidence of connections between these two disorders, which have started with the Gillberg’s study in 1983, to searching for more effective and holistic treatment of this comorbidity. The latter is known to contribute to more severe courses and worse prognosis, which is probably related to the obstacles in both diagnosing as well as treating. Since AN usually starts in early adolescence and high-functioning ASD children seem to begin struggling with increased pressure in adolescence, while various comorbidities can occur, it is important to improve the treatment of this comorbidity in young patients and to tailor it specifically in terms of diagnosing. In this paper, a literature review is conducted on common features and promising treatment possibilities. We describe cognitive remediation therapy and the promising pharmacotherapeutic candidate oxytocin with a special focus on adolescents.